Public-Private Partnership with reference to the experience of Saudi Arabia Kingdom - Halloufi, Sofiane (Finance and Business Economies Review, 2022)
This study aims to shed light on the increasing importance of the public-private partnership in the Saudi Arabia Kingdom, and the growing of available opportunities to attract private investments for many sectors such as aviation, water and port management, as well as clarifying challenges and obstacles of this type of contracting, and requirements for the successful partnership between public and private sectors in order to clarify and crystallize requirements and foundations of the real partnership between them in setting economic policies in order to advance the Saudi economy and achieve the desired economic development in the Kingdom’s Vision 2030. The study concluded that the partnership between public and private sectors, if it has the right structure, can be developed successfully, that’s what has been proved by the actual progress made by the Kingdom by opening new sectors and reforming laws and regulations, which led to an increase interest in partnership projects between the public sector and the private one. Thus, it will contribute to an increase number of partnership projects in the coming years with international, regional and local partners.